Disentangling director attributes: Human capital versus social capital of directors - Angela Andersen; Alexandre Garel; Aaron Gilbert; Alireza Tourani-Rad (Journal of Risk and Financial Management, 2022)
This study seeks to disentangle the human capital and the social capital of directors to improve our understanding of the value that directors bring to their boardroom. Employing social network analysis (SNA) to measure the social capital of directors and using a unique and comprehensive sample of New Zealand publicly listed firms over the period of 2000-2015, we find a positive and significant relationship between the human capital and the social capital of directors, where the human capital appears to predict changes in social capital. We contend that the growing literature in the area of corporate finance and governance investigating the impact of characteristics of directors on corporate outcomes, need to take note of the complementary impact that social capital can have in addition to human capital.
Keywords: C33; G32; G3; 650; corporate governance; board effectiveness; board of directors; human capital; social capital; social network analysis